Sistem Pendeteksi Kebocoran Gas Berbasis Arduino Menggunakan Nodemcu Dan Bylink - Kardi Chan (Jurnal Sains Informatika Terapan, 2025)
The rapid advancement of Internet of Things (IoT) technology has significantly contributed to the development of smart home systems that improve safety, comfort, and efficiency in modern households. This study aims to design and implement a gas leak detection system based on Arduino, integrated with NodeMCU ESP8266 and the Blynk application as a real-time monitoring and notification platform. The system employs an MQ-2 sensor to detect LPG gas concentration in the surrounding air. When the gas concentration exceeds a certain threshold, the system automatically activates a buzzer and LED indicator as a local alarm, while simultaneously sending a notification to the user’s smartphone via the Blynk application. Experimental results demonstrate that the system responds rapidly, with a delay of less than one second, and maintains good detection accuracy and network stability. Furthermore, the system is cost-efficient, user-friendly, and capable of remote monitoring, making it an effective solution for enhancing home safety. The integration of Arduino, NodeMCU, and Blynk provides a reliable and scalable IoT-based framework that can be expanded for future smart home security applications.